2016
DOI: 10.1111/den.12661
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter randomized controlled study to assess the effect of prophylactic clipping on post‐polypectomy delayed bleeding

Abstract: Background and Aim: Prophylactic clipping has been widely used to prevent post-procedural bleeding in colon polypctomy. However, its efficiency has not been confirmed and there is no consensus on the usefulness of prophylactic clipping. The aim of the present study was to evaluate the preventive effect of prophylactic clipping on post-polypectomy bleeding.Methods: A multicenter randomized controlled study was conducted from January 2012 to July 2013 in Japan. Patients who had polyps <2 cm in diameter were divi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 13 publications
1
51
2
1
Order By: Relevance
“…In the present study, clips were partially or completely displaced in 15 of 27 lesions (55.6%) at the time of PPB, therefore the dislocation of clips might be one of the reasons for PPB. However, the facts that clips remained in place in almost half of the lesions with PPB in the present study, and that PPB occurrences in lesions with prophylactic clips in previous studies suggest that the procedure could not prevent PPB completely in clinical practice. Furthermore, the effect was not enough for the HB group because of the high incidence of PPB despite the procedure.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…In the present study, clips were partially or completely displaced in 15 of 27 lesions (55.6%) at the time of PPB, therefore the dislocation of clips might be one of the reasons for PPB. However, the facts that clips remained in place in almost half of the lesions with PPB in the present study, and that PPB occurrences in lesions with prophylactic clips in previous studies suggest that the procedure could not prevent PPB completely in clinical practice. Furthermore, the effect was not enough for the HB group because of the high incidence of PPB despite the procedure.…”
Section: Discussioncontrasting
confidence: 78%
“…Uninterrupted use of oral anticoagulants or discontinuing warfarin without heparin‐bridging therapy for polypectomy might have a potential to reduce PPB without increasing the risk of thromboembolic events; however, the evidence of how to manage anticoagulants for polypectomy is still scarce. Prophylactic clip closure might reduce the risk of PPB, although the efficacy of the procedure remains controversial . In the present study, clips were partially or completely displaced in 15 of 27 lesions (55.6%) at the time of PPB, therefore the dislocation of clips might be one of the reasons for PPB.…”
Section: Discussionmentioning
confidence: 56%
“…Some reports described that prophylactic clipping prevent DPPB 37 38 39 . In contrast, some studies have demonstrated that there was no difference 40 41 42 43 . In this study, the HP group had a significantly larger number of clips used for closure of the mucosal defect.…”
Section: Discussionmentioning
confidence: 89%
“…Therefore, prophylactic clipping might not prevent PPB. As for EMR and HP, it was reported that prophylactic clipping showed no efficacy for prevention of PPB [29], as was the case for CP; however, a larger number of cases is necessary to prove this hypothesis.…”
Section: Discussionmentioning
confidence: 99%